په‌یوه‌ندی ئاستی به‌كارهێنانی ته‌كنه‌لۆجیای زانیاری و په‌یوه‌ندیكردن به‌پاڵنه‌ری فێربوون و زیره‌كی هه‌ڵچوونی‌ لای خوێندكــــــارانی زانـــــــكۆی سلێمانـــــــی (مستل) - خالد, حسن فخرالدین; عبدالله, ئاكۆ محمد; محمد, سه‌ركه‌وت جمال (Sulaimani Journal for Humanities, 2022)
The aim of this study is to discover the relationship between the use of ICT, Learning motivation and Emotional Intelligence among students of Sulaimani University,to knowing their differences based on the following demographic variables: (gender,specializatio)branches, Knowing the number of hours of using information and communication technology and their differences in the level of Learning Motivation and Emotional Intelligence, the researcher has used a descriptive and correlative method as a method of the study. The participants were the students of Sulaimani University for morning class which were (21161) students.the sample consisted of(995) male and female students who were randomly chosen from(21161)students. The researcher has used ICT measurement which was created by the researcher, as well as the Learning Motivation and Emotional Intelligence measurement which were prepared by the resercher.the resercher has used these techniques in IBM SPSS(Mean,Std-deviation,T-Test,Pearson and one way ANOVA. the results indicated that:The level of using ICT ,Learning motivation and Emotional Intelligence were high among students.There are no significant differences among students in using ICT betwenn genders.There are significant differences between specializations in favor of scientific. Learning Motivation and Emotional Intelligence are significant differences between genders in favor of males and between specializations in favor Scientifics. The relationship between using ICT with learning motivation and Emotional Intelligence is a direct relationship,as the level of one increase when the other increases, finally the results show that the hours of using ICT will increase the level of Learning Motivation and Emotional Intelligence. In light of the results,the researcher presents some recommendations and suggestions.